Czynniki sukcesu menedżerów w opinii słuchaczy szkół zarządzania - badania międzynarodowe - Mesjasz, Joanna (Managerial success factors in the opinion of management schools students - international research, 2006)
“Success” is one of the key words in modem world and at the same time it is also one of the most important targets of professional activity. Young people studying and going to become managers believe in success as supreme power and they think that prestige and social position define person’s value. Strongly pressed young generation of 20-30 years undertakes challenges making particular calculation of possible profits and necessary costs of the professional activity. They use patterns present in common society of competition and consumption. They are ready to sacrify a lot: value structure, own principles and ideals, they want to be tough, have no bad conscience. They are ready to pay for the success with the free time, health, lack of hobbies, they resign their dreams. Having destructive lifestyle they are afraid to stay outside of the run, they are mobilized, pressed with competition and commitments. Particularly interesting is the fact that in the three countries of research the balance of professional costs and profits looks alike in the eyes of all young people, however different factors influence it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 89-98